Investigation of Seroprevalence of Toxoplasmosis in Horses and Donkeys in Muş Province of Turkey - Kirbas, Akin (Journal of the Hellenic Veterinary Medical Society, 2022)
The purpose of this study was to determine the seroprevalence of Toxoplasmosis in equidae in the province of Muş, Turkey. The study material consisted of 210 equidae including 159 horses and 51 donkeys in Mus province. In serum samples, anti-Toxoplasma gondii antibodies and titers were detected using Sabin Feldman Dye Test (SFDT). Seropositivity was found in 115 (54.76 %) of the 210 equidae tested in the study. The rate of seropositivity in donkeys (92.16%) was higher than the rate in horses (42.77%), and statistical significance was observed (P<0.001). T. gondii antibody was detected in 68 (42.77%) of the horse sera examined by SFDT. When T. gondii seropositivity was evaluated according to gender, it was found to be 47.92% in females and 32.92% in males. No statistical difference was observed between the gender groups (P> 0.05). When T. gondii seropositivity was evaluated according to age, seropositivity rate in the equidae older than 10 years was found to be higher as 46.67%, but no statistical significance was observed among the age groups. T. gondii antibody was detected in 47 (92.16%) of donkey sera examined by SFDT. When T. gondii seropositivity was evaluated according to gender, the rate of seropositivity was found to be 89.47% in females and 93.75% in males. No statistical significance was observed between the gender groups (P>0.05). When T. gondii seropositivity was evaluated according to age, the seropositivity rate in those older than 10 years was found to be higher as 96.30%, but no statistical significance was observed among the age groups (P>0.05). As a result of scanning the equidea in Muş province by SFDT, seropositivity rate was found as 42.77% in horses and 92.16% in donkeys. Keywords: Donkey, Horse, SFDT, Toxoplasma gondii, Toxoplasmosis